The Politics of Migration in the 21st Century: Employing Systemism to Advance Research Strategies - Jeannette Money (Social Sciences)
This article introduces systemism as a method of evaluating the expanding research agenda on the politics of migration. Systemism is a graphic method for presenting academic research concisely. It provides three methods of advancing the research agenda: elaboration, systematic synthesis, and bricolagic bridging. I employ two of these methods to follow the evolution of research on states’ migration policies from the 1990s to the 2020s, providing a critique of the research and suggesting methods for advancing our knowledge of this politically important policy issue. The article provides a short overview of systemism, and then illustrates its application through the presentation of two articles in graphic form: “No Vacancy. The Political Geography of Immigration Control in Advanced, Market Economy Countries” by Jeannette Money, and “The Migration State in the Global South: Nationalizing, Developmental, and Neoliberal Models of Migration Management”, authored by Fiona Adamson and Gerasimos Tsourapas. Elaboration is employed to expand the systemist presentation of “No Vacancy”, to communicate causal mechanisms more thoroughly. The next section employs systematic synthesis to bring together the two articles and to engage the research agenda on the politics of migration policy. The past 30 years have witnessed an expansion of the definition of migration management strategies captured by the four-fold typology proposed by Adamson and Tsourapas. However, continuing to pay attention to the domestic politics of migration management would help to illuminate variation among states within each category. Both articles acknowledge structural factors that constrain or provide opportunities for states’ migration policy choices, but neither develops a clear picture of the systemic factors that shape international mobility and the policy choices of states in the international system. The conclusions point to a continuing expansion of the research agenda along these three dimensions.